Pemahaman Makna Bahasa Anak Kelas 1 SD Dalam Pembelajaran Online: Kajian Psikolinguistik - Yati Suwartini; Endry Boeriwati; Zainal Rafli (Risenologi, 2022)
Language is a medium that children can use to acquire cultural values, morality, religion and other community values. After children acquire the language consciously or not, children will understand the meaning of the language said and done. This study aims to determine the understanding of the language of 1st grade elementary school students and what factors affect their understanding of the meaning of language in terms of psycholinguistic studies. The method in this research is descriptive qualitative research. Researchers made observations on the object of research, namely the students and teachers of SD Class 1 during the interaction in the online class. To get more in-depth information regarding the understanding of different students, the researcher distributed questionnaires to the teachers. The results showed that the students interpreted the decoding of the message conveyed by the teacher, the students did it with the meaning of the words that they had understood based on their experience, knowledge, needs, and abilities. Understanding the meaning of language in different children is caused by environmental factors, facilities or facilities, and teacher factors. This study has limitations in data collection which is only limited to speech that occurs in online classes.